Effect of Gluten Free Flours on Sensory Properties of ‘Banana Blossom Keropok Lekor’ - Hamdin, Nor Amirah Sahirah; Kormin, Faridah (Enhanced Knowledge in Sciences and Technology, 2025)
Keropok lekor is a well-known fish-based traditional dish that originated in Terengganu, Malaysia. It is typically cooked by either boiling or frying and is known for its unique and chewy texture. Unlike the traditional version made with fish, this keropok lekor uses banana blossom as the main ingredient, with a fibrous structure resembling meat fibre, making it an excellent plant-based alternative while offering distinctive flavour and texture. This study aims to develop a new version of banana blossom keropok lekor by including various gluten-free flours. The objective is to evaluate the nutritional composition, physical properties, and sensory perceptance of the banana blossom keropok lekor with improved nutritional value while addressing the challenges of creating non-allergic and vegan-friendly alternatives. Formulations containing sweet potato starch, taro flour, and arrowroot flour are used to enhance the nutritional profile of banana blossom keropok lekor. The cooked banana blossom keropok lekor will be boiled, cooled to ambient temperature, vacuum-sealed, stored at -18°C for further analysis. This study will evaluate the nutritional composition, physical properties, and sensory attributes of the product, focusing on the impact of substituting wheat flour with gluten-free alternatives, aiming to develop a healthier and more nutritious snack that is gluten-free, allergen-free, lower in calories, and higher in dietary fiber compared to traditional keropok lekor.